Foreign Aid and Consumption Smoothing : Evidence From Global Food Aid - Tiongson, Erwin (IMF Working Papers; Working Paper ;, 2003)
Global food aid is considered a critical consumption smoothing mechanism in many countries. However, its record of stabilizing consumption has been mixed. This paper examines the cyclical properties of food aid with respect to food availability in recipient countries, with a view to assessing its impact on consumption in some 150 developing countries and transition economies, covering 1970 to 2000. The results show that global food aid has been allocated to countries most in need. Food aid has also been countercyclical within countries with the greatest need. However, for most countries, food aid is not countercyclical. The amount of food aid provided is also insufficient to mitigate contemporaneous shortfalls in consumption. The results are robust to various specifications and filtering techniques and have important implications for macroeconomic and fiscal management.